2020
DOI: 10.1007/s11414-020-09739-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Youth Substance Use: We Need More than Good Intentions

Abstract: An "epidemic hidden in a pandemic". 1(np) That is what Andrea Raby, D.O. of Bayless Integrated Healthcare, calls the threat to our youth who are now at increased risk of substance use disorder and overdose in the wake of the COVID-19 pandemic. "This is always a vulnerable time during this period in their growth, in their development, in their growth of their identity, and often times what helps our adolescent population is structure and predictability and of course with COVID, this renders everything the oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Demarest (2020) suggested the pandemic might increase depression among adolescents, leading to increased substance use, constituting an “epidemic hidden in a pandemic”. Ingoglia (2020) suggested disruption in daily routines for adolescents (through canceled in-person classes, athletics, and extracurricular activities) might make them particularly vulnerable. He concluded, “We know little about the emerging threats of COVID-19 on our youth” (p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Demarest (2020) suggested the pandemic might increase depression among adolescents, leading to increased substance use, constituting an “epidemic hidden in a pandemic”. Ingoglia (2020) suggested disruption in daily routines for adolescents (through canceled in-person classes, athletics, and extracurricular activities) might make them particularly vulnerable. He concluded, “We know little about the emerging threats of COVID-19 on our youth” (p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Common behavioral problems include performance avoidance, decreased work enthusiasm and physical activity, increased dependence on families, and disorderly lifestyle and self-management. Health care workers may also experience unhealthy lifestyle activities, such as smoking, drinking, staying up late, and overeating; or blind behaviors, such as panic buying and stockpiling of disinfection supplies, food, drugs, etc [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adolescent substance use is a national problem and while decreasing with some substances, continues to persist and escalate in others [ 5 , 6 ]. The COVID-19 pandemic has added further urgency to addressing this issue as adolescents may turn to substances to cope or self-medicate during this difficult time [ 10 12 ]. Currently there is lack of family-based, universal substance use prevention programming to reduce and/or delay substance use initiation among youth that reduce participant burden, are easily disseminated, and sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…Given the stress and increased mental health problems among youth [ 10 ], the COVID-19 pandemic has raised some concerns regarding adolescent substance use, although evidence is limited [ 11 , 12 ]. One study of Canadian adolescents reported the proportion of adolescents who reported one or more substance-using days within a period of three weeks pre-COVID compared to 3 weeks during COVID increased significantly from 0.76 to 0.96 (p = 0.02) and from 0.94 to 1.10 (p = 0.01) for alcohol and marijuana, respectively [ 13 ].…”
Section: Introductionmentioning
confidence: 99%